Synthesis of WO3−x nanomaterials with controlled morphology and composition for highly efficient photocatalysis. Issue 8 (28th April 2016) - Shen, Zhenguang; Zhao, Zengying; Qian, Jingwen; Peng, Zhijian; Fu, Xiuli
Abstract: Abstract : Tungsten oxide (WO3−x ) nanomaterials with controlled morphology and composition were fabricated by thermal evaporation of WO3 and S powders at different temperatures in a vacuum tube furnace. At 850 °C the obtained green particle is still of the same monoclinic WO3 phase as that of the starting powder. At a temperature between 900 and 1100 °C, the resultant dark-blue products are particle-like clusters composed of numerous monoclinic WO2.90 short nanorods, but the clusters became looser and the nanorods grew somewhat longer as the temperature increased. At a temperature between 1150 and 1250 °C, elongated and thoroughly separate purple-red monoclinic W18 O49 nanorods were obtained. The growth of the prepared WO3−x nanomaterials was controlled by a gas–solid mechanism. Their photocatalytic degradation on organic contaminants was evaluated by decomposing methylene blue (MB) in aqueous phase under sunlight, in which WO3 particles presented higher photocatalytic activity than its oxygen-deficient counterparts, WO2.90 and W18 O49 . But the W18 O49 nanorods had higher adsorption ability to MB in all the samples.